Nursing practice and education in Yemen and It’s impact during war (Indonesian Contemporary Nursing Journal (ICON Journal), 2025)
Nursing is the backbone of healthcare systems, playing a vital role in public health improvement. However, armed conflicts adversely affect this profession, particularly in education and practice. In Yemen, the ongoing conflict has led to the destruction of educational and healthcare institutions, impacting the training of nurses. A study revealed that Yemeni nurses' knowledge of Basic Life Support (BLS) was inadequate, with only 53.65% of correct responses indicating training gaps during the war. Practitioners also face challenges such as shortages of medical resources, power outages, and the migration of skilled medical personnel. Despite these difficulties, nurses in conflict zones have demonstrated resilience and adaptability, enhancing their clinical skills. This article highlights the impact of war on the nursing profession in Yemen, focusing on challenges in practice and education.
Keywords: nursing practice in Yemen; nursing education in Yemen; practice and education impact during war